Multiresistensi dan Akumulasi Acinetobacter sp. IrC2 terhadap Logam Berat - Wahyu Irawati; Aaron Hasthosaputro; Lucia Kusumawati (Jurnal Biologi Papua, 2020)
The increasing industrial activity in Indonesia, that is not equipped with appropriate waste treatment, has caused an increase of heavy metal contaminants in water bodies. Heavy metals contamination such as copper (Cu), mercury (Hg), cadmium (Cd), and lead (Pb) contamination in water bodies have endangered aquatic life and public health. For this reason, it is urgently important to lower down the concentration of heavy metal pollutants in the water bodies surrounding industrial areas. Compared to chemical remediation, bioremediation of heavy metal by using indigenous bacteria is more effective and economical, since it can be applied in situ directly and be used repeatedly. Acinetobacter sp. IrC2, used in this study, is Indonesian indigenous bacteria isolated from the industrial waste treatment facility in Rungkut, Surabaya. This study aims, firstly, to investigate the heavy metal multiresistance of Acinetobacter sp. IrC2 against mercury, cadmium, and lead. Secondly, this study intends to examine its bioaccumulation capacity for single and heavy metal alloys. The heavy metal multiresistance test was carried out by measuring the minimum heavy metal concentrations that inhibit bacterial growth (Minimum Inhibitory Concentration/MIC). The bioaccumulation capacity was measured using an atomic absorption spectrophotometer (AAS).  It is shown that Acinetobacter sp. IrC2 has high multiresistance to mercury, cadmium, and lead with MIC values of 12 mM, 8 mM, and 18 mM, respectively. Furthermore,  it is also resistant to  heavy metal mixture of 4.5 mM.  The mechanism of bacterial resistance in response to heavy metal toxicity, in general, is by accumulating heavy metals in the cells. The highest amount of accumulated heavy metals identified, from bacteria grown in the medium contains a mixture of heavy metals, were 0.023 mg, 0.084 mg, 0.684 mg, and 1.476 mg per gram of cell dry weight for copper, mercury, cadmium and lead respectively.  In conclusion, Acinetobacter sp. IrC2 is a promising heavy metal bioremediation agent due to its heavy metal multiresistance and accumulator characteristics.  Key words: Acinetobacter sp. IrC2; cadmium; copper; lead; merkuri